The FORA Framework A Fuzzy Grassroots Ontology for Online Reputation Management - Portmann, Edy. (Fuzzy Management Methods, 2013)
Online reputation management deals with monitoring and influencing the online record of a person, an organization or a product. The Social Web offers increasingly simple ways to publish and disseminate personal or opinionated information, which can rapidly have a disastrous influence on the online reputation of some of the entities. The authorfocuses on the Social Web and possibilities of its integration with the Semantic Web as resource for a semi-automated tracking of online reputations using imprecise natural language terms. The inherent structure of natural language supports humans not only in communication but also in the perception of the world. Thereby fuzziness is a promising tool for transforming those human perceptions into computer artifacts. Through fuzzy grassroots ontologies, the Social Semantic Web becomes more naturally and thus can streamline online reputation management. Forreaders interestedin the cross-over fieldof computer science, information systems, and social sciences, this bookis an ideal source for becoming acquainted with the evolving field of fuzzy online reputation management in the Social Semantic Web area.